2020
DOI: 10.1364/boe.386612
|View full text |Cite|
|
Sign up to set email alerts
|

Estimating intracranial pressure using pulsatile cerebral blood flow measured with diffuse correlation spectroscopy

Abstract: Measuring intracranial pressure (ICP) is necessary for the treatment of severe head injury but measurement systems are highly invasive and introduce risk of infection and complications. We developed a non-invasive alternative for quantifying ICP using measurements of cerebral blood flow (CBF) by diffuse correlation spectroscopy. The recorded cardiac pulsation waveform in CBF undergoes morphological changes in response to ICP changes. We used the pulse shape to train a randomized regression forest to estimate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 43 publications
2
56
0
Order By: Relevance
“…Derivatives of the above described static, dynamic, and pseudo-dynamic measurements have been proposed in order to reduce the need of invasive ICP sensors and improve reliability. Such methods often replace ICP or ABP with other hemodynamic measurements such as hemoglobin concentrations, tissue oxygenation or blood volume and summaries of them can be found elsewhere [15,[23][24][25], including non-invasive diffuse optical methods used in this article [26,27]. Despite many decades of research and a large variety of measurement methods, a consensus on the effectiveness and use of CA measurements to guide clinical treatment has not yet been reached.…”
Section: Introductionmentioning
confidence: 99%
“…Derivatives of the above described static, dynamic, and pseudo-dynamic measurements have been proposed in order to reduce the need of invasive ICP sensors and improve reliability. Such methods often replace ICP or ABP with other hemodynamic measurements such as hemoglobin concentrations, tissue oxygenation or blood volume and summaries of them can be found elsewhere [15,[23][24][25], including non-invasive diffuse optical methods used in this article [26,27]. Despite many decades of research and a large variety of measurement methods, a consensus on the effectiveness and use of CA measurements to guide clinical treatment has not yet been reached.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, non-invasive methods for measuring ICP have emerged, including fundoscopy examinations and optical coherence tomography (OCT) (21), flash visual evoked potential (VEP) (22), IOP and venous ophthalmodynamometry (23), tympanic membrane displacement (24), electroencephalogram (25), retinal blood pressure (26), blood flow velocity pulsatility index (27), and cerebral blood flow (28). Due to the large variation and difficulty in implementation, some of these methods are gradually reduced, however, there are several non-invasive methods to detect ICP, which are considered to be more useful.…”
Section: Review Articlementioning
confidence: 99%
“…A recent study using invasive monitoring methods simultaneously recorded ICP and CBF waveform in non-human primate, reported that a higher ICP led to a broadening and rightward shift of the ICP and CBF pulse wave [50] , although the strength of this effect differed between subjects. In patients with NPH underwent CSF drainage, the arterial pulse became thinner, and peaked earlier than pre-drainage [43] .…”
Section: Interpretation Of the Prolonged Ttpmentioning
confidence: 99%